BUKU ESAI FOTOGRAFI “SINAR HARAPAN DI BUKIT GREEN VILLAGE“ UNTUK MENGOPTIMALKAN OBYEK WISATA FLYING FOX GEDANGSARI GUNUNG KIDUL YOGYAKARTA - Puji Handayani Putri (Universitas PGRI Yogyakarta, 2019)
Abstract Gedangsari Subdistrict in Gunungkidul is the sub-district which is the northernmost and directly borders with Kecamatan Bayat, Klaten Regency, Central Java. In Gedangsari sub-district it has beautiful natural potential and is still natural and beautiful, one of which is Green Village. Green Village has the longest Flying Fox attraction in Southeast Asia. But unfortunately the lack of publications makes the tourism potential less known to the public. So there needs to be an effort to optimize the tourism potential to be known by the community. One of the authors' efforts is to design a photographic essay book entitled